She, her Fostering gender equality (SDG 5) through audiovisual fiction: Case Study of the Transmedia Women’s Football Series Irabazi Arte! and its Impact on the Generation Alpha - Junguitu-Angulo, Leire; Osuna-Acedo, Sara (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This research examines the second season of the transmedia children's series Irabazi Arte! in relation to promoting empowerment and gender equality (Sustainable Development Goal 5). Irabazi Arte!, broadcast on Basque public television (EITB), is produced entirely in Basque and its central storyline is women's football. Using a mixed methodology, it will be analysed if and how gender equality is promoted in its transmedia universe and if it has the potential to have an impact on its young audience. A quantitatively and qualitatively positive representation of SDG 5 is found. This transmedia narrative fits the characteristics of the Generation Alpha and contributes to the progress of gender equality through educommunication, promoting equality in the Generation Alpha